Air quality public policies and their implications for densely populated urban areas in Brazil - Xavier, José Carlos de Moura; de Sousa Júnior, Wilson Cabral; Martins, Maria Paulete Pereira (Sustainability in Debate, 2017)
Due to the current growth of the Brazilian population income and energy consumption and an increase in the population density in urban areas, air quality in the crowded Brazilian cities is being questioned. In searching for a solution we analyzed both the Brazilian and Regional (São Paulo state) public policies of air quality that have been issued since 1981 by confronting them to the air quality official indexes. Following the growth of the national vehicle fleet, 48.8 million in 2012 from 9.3 million in 1980, the total carbon dioxide emissions tripled. At regional level, PM2.5 measurements have been carried out systematically since 1999 in the Metropolitan Region of São Paulo city, the largest Brazilian city, with 19.7 million inhabitants, and more than 7 million vehicles powered mainly by fossil fuels. Although the numbers are still above the state standard to be reached (10µg.m-3), there was a decrease on the annual average in 2008-2015 compared with 2001-2007. This was partially due to the limits established for new vehicles by federal programs. The analysis indicated that the reduction of air pollutants emission will be more easily achieved based on strategies that combine policies supported by current laws, government and private sector agreements and the community engagement.